2021
DOI: 10.1088/1361-6439/ac2e46
|View full text |Cite
|
Sign up to set email alerts
|

Power enhancement of MEMS vibrational electrostatic energy harvester by stray capacitance reduction

Abstract: We report a design method to enhance the output power of vibrational microelectromechanical system (MEMS) electrostatic energy harvesters by reducing the reactive power that does not contribute to the net output. The mechanism of enhancing the active current while reducing the reactive current is analytically studied using an equivalent circuit model of electret-based velocity-damped resonant-generator. Reduction of the internal parasitic capacitance associated to the contact pads and electrical interconnectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…This technology has gained considerable attention as a promising battery‐free solution 5 . To date, the scavenging of mechanical and vibrational kinetic energy has been achieved through the implementation of three prevailing energy conversion mechanisms, specifically, the piezoelectric, 6 electromagnetic, 7 and electrostatic 8 effects. Piezoelectric energy harvesters have gained considerable global attention as a result of their high energy density and ease of miniaturization in fabrication 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This technology has gained considerable attention as a promising battery‐free solution 5 . To date, the scavenging of mechanical and vibrational kinetic energy has been achieved through the implementation of three prevailing energy conversion mechanisms, specifically, the piezoelectric, 6 electromagnetic, 7 and electrostatic 8 effects. Piezoelectric energy harvesters have gained considerable global attention as a result of their high energy density and ease of miniaturization in fabrication 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The stray capacitance can be lowered to some extent using an SOI of a thick BOX layer as reported elsewhere. (36) Nonetheless, an equivalent circuit model suggested that the BOX layer thickness needed to eliminate the effect of the stray capacitance would be more than 10 µm, which is not practically available from a cost and residual-stress viewpoint of SOI wafers.…”
Section: Introductionmentioning
confidence: 99%
“…There are various types of devices for collecting vibration energy. These can be classified into electromagnetic harvesting devices [ 9 , 10 , 11 ], electrostatic harvesting devices [ 12 , 13 , 14 ], piezoelectric harvesting devices [ 15 , 16 , 17 ], and frictional electric harvesting devices [ 18 , 19 , 20 ] according to their different principles of power generation. The operating principle of electromagnetic energy harvesting devices is based on Faraday’s law of electromagnetic induction, and their energy recovery devices are simple and do not require separate power supplies [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%